Réponses

Meilleure réponse !
2013-01-15T15:01:02+01:00

Bonjour,

 

1) (3x+5) (3x-5) - 2 (3x-5) ² ≤ 0

 

(3x-5)(3x+5 - 2 (3x-5))  ≤ 0

 

 (3x-5)(3x+5 - 6x+10)  ≤ 0

 

(3x-5)(-3x+15)  ≤ 0

 

A = 3(3x-5)(-x+5)  ≤ 0

 

x1 = 5/3    et    x2 = 5

 

x        -inf            5/3           5            +inf

(3x-5)           -      0      +           +          

(-x+5)          +              +     0     -           

A                  -      0      +      0     -  

 

S= ] -inf  ; 5/3  ]  U  [ 5 ; +inf [    

 

       

 

2) B = (8x+1) (-3x+4) (6x+7) ≥ 0

 

x1 = -1/8   ;  x2 = 4/3  ;  x3 = -7/6

 

x            -inf          -7/6            -1/8             4/3            +inf

(8x+1)             -               -          0       +                +

(-3x+4)           +              +                  +        0       -            

(6x+7)             -       0     +                  +                 +              

B                     +       0     -          0      +         0      -                    

 

 

S= ] -inf  ; -7/6  ]  U  [ -1/8 ; 4/3 ]

 

 

3) (2x-3) ² > (3x+7) ²

 

(2x-3) ² - (3x+7) ² > 0

 

 

4x²-12x+9-(9x²+42x+49 > 0

 

4x²-12x+9-9x²-42x-49 > 0

 

-5x²-54x-40 > 0

 

C = 5x²+54x+40 < 0

 

delta = 54²-(4*5*40) = 2116 = 46²

 

x1 =( -54+46)/10 = -8/10 = -4/5

 

x2 = ( -54-46)/10 = -100/10 = -10

 

C < 0

 

S= ] -10 ; -4/5[

 

4) x ³ < 25 x

 

 x ³-25x < 0

 

 x(x²-25) < 0

 

D = x(x+5)(x-5) < 0

 

x            -inf          -5              0               5            +inf

x                     -               -       0      +              +

(x+5)              -     0      +                +             +            

(x-5)              +             +                +      0      -              

D                   +      0      -        0     +      0      -        

 

D < 0    

 

S = ]-5 ; 0 [ U ]-5 ; 0 [5 ; +inf [

 

J'espère que tu as compris

a+